Clinical Evalution of the Results of Jewett Nail Plate Fixation for Trochanteric Fracture - Dam, Bipul Kumar (TAJ: Journal of Teachers Association, 2009)
This study was carried out on 53 patients admitted in the Department of Orthopaedics, Rajshahi Medical College who were admitted with trochanteric fractures and were operated. Among them, 37 (69.81%) patients had their fracture due to fall on the ground during walking and 16 (30.19%) sustained injury due to road traffic accident. Regarding type of fracture 30 (56.60%) had stable fracture and 23 (45.40) had unstable fracture. doi: 10.3329/taj.v15i2.3913 TAJ December 2002; Vol.15(2): 78-80